Evaluation of Antibiotic Use in Paediatric Inpatients Diagnosed with Urinary Tract Infection at a Private Hospital in Yogyakarta - Christina Ika Sindudisastra; Titien Siwi Hartayu (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2026)
The prevalence of urinary tract infections (UTIs) among Indonesian children remains high, with antibiotics as the primary therapy. This study evaluated the patterns and appropriateness of antibiotic use in pediatric inpatients with UTIs at a private hospital in Yogyakarta in 2023, based on the hospital’s Clinical Practice Guideline (CPG) using a descriptive-analytic research with mix-methods study design including both quantitative and qualitative data collection. Data collection involved retrospective medical record review of 55 patients, prospective observation of therapeutic management, and in-depth interviews with prescribers and hospital administrators. Medical record review showed that 98% of patients received antibiotics, with 100% appropriateness in indication and patient, 63.54% in antibiotic selection, and 21.82% in dosing. Common antibiotics included injectable ceftriaxone (40.54%), cefotaxime (18.82%), and gentamicin (16.22%). Observations indicated general adherence to CPGs, while interviews revealed prescribing decisions were influenced by patient condition, clinical progress, guidelines, and prescriber experience. Hospital management expressed support for rational antibiotic use through funding and infrastructure provision. Despite generally appropriate prescribing practices, gaps remain in antibiotic selection and dosing. Suggested strategies include combined educational interventions for prescribers and managerial measures to strengthen and implement CPGs, aiming to optimize antibiotic use and reduce the risk of resistance.